The Effect of Non-Performing Loans (NPLs), Return On Equity (ROE) and Capital Adequacy Ratio (CAR) on the Profit Growth of State-Owned Banks 2014-2023 - Kristiana Suwantri; Anita Roosmawarni; Budi Wahyu Mahardhika; Didin Fatihudin (P3I UMSurabaya, 2025)
Stable profit growth reflects a bank’s operational efficiency and resilience in responding to market dynamics. Increasing profits provide opportunities for reinvestment, innovation, and business expansion, thereby strengthening long-term competitiveness. This study employed purposive sampling with a sample of four state-owned banks (BUMN) and data processing was conducted using EViews 12 software. The best-fit model identified was the Fixed Effect Model (FEM). The results indicate that NPL, ROE, and CAR have a significant simultaneous effect on profit growth. Partially, ROE and CAR have a significant influence, while NPL does not. The R-squared value of 90.32% shows that these independent variables explain a substantial portion of the variation in profit growth. Steady profit growth reflects the bank's operational efficiency and resilience in the face of market dynamics. Increased profit growth provides opportunities for banks to reinvest, innovate, and expand their businesses, thereby strengthening long-term competitiveness. This study uses a purposive sampling method with a sample of 4 state-owned banks (Mandiri, BRI, BNI, BTN) and data processing using EViews 12 software. The best model obtained is the Fixed Effect Model (FEM). The results of the study show that NPL, ROE, and CAR simultaneously have a significant effect on profit growth. Partially, ROE and CAR have a significant effect, while NPLs do not. The R-squared value of 90.32% indicates that the three independent variables explain most of the variation in profit growth.